Upaya Mengatasi Bullying melalui Edukasi Pendidikan Karakter - Anggraini, Ratna Dwi; Nopriansyah, Untung; Setiawan, Rendi; Adelia, Anggita; Arinda, Devi; Maharani, Putri (Journal of Social Empowerment, 2024)
Bullying is a form of child abuse that is perpetrated by peers against someone (child) who is "lower" or weaker in order to gain certain benefits or satisfaction. The culture of bullying (violence) in the name of seniority still continues among students in elementary schools, bullying usually occurs repeatedly, some are even carried out in a planned manner. The method used in this research is qualitative. Results of the activity In the implementation of community service The location of community service was carried out at SDN 7 Tanjung Raya, on August 5 2023. The duration of this activity was carried out for 4 hours, namely at 08.00 - 11.00 WIB. what has been explained in this socialization, after carrying out this socialization the author hopes that students can have good insight to be able to respond to association in this millennial era which is in accordance with the view of the Islamic religion. This socialization also describes the negative impact of bullying and helps students to be able to fortify themselves from bullying behavior and from the ease of obtaining negative information. This is of course something that must be done by educational institutions and parents to contribute in looking after students so that they can become children with good character who can later be useful for the community/country.